2014
DOI: 10.1177/1362361313518994
|View full text |Cite
|
Sign up to set email alerts
|

Pain as a predictor of sleep problems in youth with autism spectrum disorders

Abstract: Evidence suggests that pain interferes with sleep in youth with developmental disabilities. This study examined the relationship between pain and sleep problems in a sample of youth with parent-reported autism spectrum disorder (N = 62). Mothers reported on standardized measures of pain and sleep problems. Youth demonstrated atypically high levels of both observed pain and sleep problems. Pain predicted overall sleep disturbance and three specific sleep problems: sleep duration, parasomnias, and sleep-disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 52 publications
1
25
0
5
Order By: Relevance
“…Sleep disturbances in individuals with ASD can be ascribed to biological, psychological, and/or social/environmental factors. Comorbid medical conditions may also predispose to sleep disturbances in people with ASD such as attention-deficit/hyperactivity disorder (Liu et al 2006), asthma (Liu et al 2006), epilepsy (Liu et al 2006), pain (Tudor et al 2014), and gastrointestinal problems (Mannion et al 2013). Most importantly, clinical characteristics and psychiatric comorbidities in ASD, such as pathological anxiety (Mazurek and Petroski 2014;Nadeau et al 2014) and depression, predispose to sleep disorders (Richdale and Baglin 2015).…”
Section: Etiology Of Sleep Dysfunction In People With Asdmentioning
confidence: 99%
“…Sleep disturbances in individuals with ASD can be ascribed to biological, psychological, and/or social/environmental factors. Comorbid medical conditions may also predispose to sleep disturbances in people with ASD such as attention-deficit/hyperactivity disorder (Liu et al 2006), asthma (Liu et al 2006), epilepsy (Liu et al 2006), pain (Tudor et al 2014), and gastrointestinal problems (Mannion et al 2013). Most importantly, clinical characteristics and psychiatric comorbidities in ASD, such as pathological anxiety (Mazurek and Petroski 2014;Nadeau et al 2014) and depression, predispose to sleep disorders (Richdale and Baglin 2015).…”
Section: Etiology Of Sleep Dysfunction In People With Asdmentioning
confidence: 99%
“…Tatsumi et al (2015) found that morning and/or afternoon physical activity among children with an ASD was associated with earlier sleep onsets, indicating that lower levels of physical activity can be a risk factor for sleep latency disturbances among children with ASDs. Pain-related behaviors such as comfort seeking have also been found to be correlated with sleep disorders among children with ASDs, indicating that uncontrolled pain may lead to sleep disturbances among children with an ASD (Tudor, Walsh, Mulder, & Lerner, 2015). In-room access to video games, television, and computers has also been positively correlated with sleep disturbances such as decreased sleep duration among school-aged and adolescent males with an ASD (Engelhardt, Mazurek, & Sohl, 2013).…”
Section: Other Risk Factorsmentioning
confidence: 96%
“…Reports have suggested that patients with autism spectrum are hyposensitive to different pain stimuli while patients with cerebral palsy, experience pain more frequently from musculoskeletal, neurological and gastrointestinal sites . Sleep problems are estimated in 18–37% of children with neurodevelopmental disorders such as Rett syndrome, autism and cerebral palsy . A complex bidirectional pain‐sleep relationship has emerged and poorer sleep might exacerbate pain by lowering pain thresholds .…”
Section: Average Of Single‐item Scores For Behavioural and Facial Marmentioning
confidence: 99%